2016
DOI: 10.1089/wound.2015.0661
|View full text |Cite
|
Sign up to set email alerts
|

Type I and II Diabetic Adipose-Derived Stem Cells Respond In Vitro to Dehydrated Human Amnion/Chorion Membrane Allograft Treatment by Increasing Proliferation, Migration, and Altering Cytokine Secretion

Abstract: Objective: Human amniotic membranes have been shown to be effective for healing diabetic foot ulcers clinically and to regulate stem cell activity in vitro and in vivo; however, diabetic stem cells may be impaired as a sequela of the disease. In this study, dehydrated human amnion/chorion membrane (dHACM) allografts (EpiFix®; MiMedx Group) were evaluated for their ability to regulate diabetic stem cells in vitro.Approach: Human adipose-derived stem cells (ADSCs) from normal, type I diabetic, and type II diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
(34 reference statements)
0
39
0
1
Order By: Relevance
“…Human adipose‐derived mesenchymal stem cells (hADMSCs) seeded onto radiosterilized human amnion have been tested in their ability to aid cutaneous wound repair in the form a biological bandage. In a study by Sánchez‐Sánchez and colleagues, AM were used as a biological scaffold for the culture and maintenance of hADMSCs, where the membranes were found to induce hADMSC to secrete IL‐10 as well as IL‐1β, whose interplay is thought to be vital for a balanced restoration of all necessary tissues . Decellularized AM has also been found to be suitable as a scaffold for the delivery of hADMSC in tissue engineering and regenerative medicine applications .…”
Section: Preclinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human adipose‐derived mesenchymal stem cells (hADMSCs) seeded onto radiosterilized human amnion have been tested in their ability to aid cutaneous wound repair in the form a biological bandage. In a study by Sánchez‐Sánchez and colleagues, AM were used as a biological scaffold for the culture and maintenance of hADMSCs, where the membranes were found to induce hADMSC to secrete IL‐10 as well as IL‐1β, whose interplay is thought to be vital for a balanced restoration of all necessary tissues . Decellularized AM has also been found to be suitable as a scaffold for the delivery of hADMSC in tissue engineering and regenerative medicine applications .…”
Section: Preclinical Applicationsmentioning
confidence: 99%
“…It is interesting to note that fetal membranes have also been used to support the growth of other stem cell types. Dehydrated fetal membranes consisting of both the amnion and chorion have been shown to support the proliferation and wound healing potential of adipose-derived stem cells from diabetic patients [98]. When implanted under the skin in a cutaneous ischemia model, the fetal membranes recruited circulating hematopoietic progenitor cells to sites of neovascularization [99].…”
Section: Fetal Membranes For Other Stem Cell Typesmentioning
confidence: 99%
“…This level of stimulation was consistent across four different samples and is similar to results from previous studies looking at placental membrane extracts. While previous research has shown the ability of extracts of other placenta tissue membrane products to stimulate migration of human umbilical vein endothelial cells, 61 ASCs, 62 and progenitor cells, 63 this is the first demonstration of this ability in a flowable placental tissue product.…”
Section: Discussionmentioning
confidence: 70%
“…Fetal chorioamniotic membranes are widely accepted as a therapeutic option for the healing of cutaneous wounds due to their immunologically privileged status and bioactive properties . Although these fetal membranes have been successfully used for the treatment of chronic wounds, the umbilical cord has garnered increasing attention as an allograft for soft tissue healing .…”
Section: Introductionmentioning
confidence: 99%
“…This was performed by characterizing the composition of the tissue, evaluating in vitro cellular responses, including, stem cell proliferation, fibroblast migration, and angiogenic potential of endothelial cells, and assessing in vivo biocompatibility and resorption in a rat subcutaneous implantation model. PURION® PLUS Processed umbilical cord tissue (dHUC, EpiCord, MiMedx Group, Inc.) is processed using a similar technology to PURION® Processed dehydrated human amnion chorion membrane (dHACM; EpiFix/AmnioFix, MiMedx Group, Inc.) . Previous studies have demonstrated that this proprietary process results in an amniotic allograft with retained biological activity, which promotes accelerated wound closure of diabetic foot ulcers and venous leg ulcers when compared with standard treatments .…”
Section: Introductionmentioning
confidence: 99%